Ergonomic Risk Assessment Among Private and Govt Middle School Children of Hayatabad, Peshawar: A Cross Sectional Survey: Ergonomic Risk Assessment among Private and Govt Middle School Children of Hayatabad - Ullah, Zakir; Changez Khan, Sardar; Akbar, Karishma; Ali Shah, Iqbal; Ahmed, Subhan; Bakht Khan, Sardar; Zaun ul Abidin, Syed; Ali, Ikram; Ahmed, Uzair (Pakistan Journal of Health Sciences, 2022)
Ergonomics is the study of fitting products for users and tasks to fit for humans. Compared to designing for children, designing for adults is simpler, but school-aged children are more susceptible to musculoskeletal problems and ergonomic risks. In Pakistani context, notably, nothing is known about ergonomic examinations in school-going youngsters. Objective: To determine and assess the ergonomic risks among private and government middle school children of Hayatabad, Peshawar. Methods: A cross sectional study was conducted in which 202 students participated. All the children studying in class 6th to 8th were recruited from different private and government middle schools of Hayatabad Peshawar. Ergonomic risk among all participants was assessed via standardized questionnaire called Rapid Upper Limb Assessment. Probability multistage sampling technique was utilized while data was analysed through SPSS version 25. Frequencies distribution, mean and standard deviation was calculated for descriptive variables, while chi square test was used to find out significant association between RULA scale and MSK pain. Results: A total of 202 students participated, ranging from 10-14 years with mean age of 12.4±1.4. Out of 202 participants only 78 participants reported MSK pain/discomforts. The most common reported painful region was the back 22 %. Most were within mild risk which was 50% followed by severe which was 13% of the total population. Conclusions: The most discomforting MSK region was the BACK followed by NECK. Pairing those with the RULA scale assessment scores, it was concluded that students were at risk of further MSK disorders if not acted upon.